2020
DOI: 10.1002/ajh.25820
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of upper extremity deep vein thrombosis with apixaban and rivaroxaban

Abstract: Randomized controlled trials leading to the approval of apixaban and rivaroxaban for venous thromboembolism (VTE) did not include patients with upper extremity deep vein thrombosis (UE‐DVT). We sought to evaluate the safety and effectiveness of rivaroxaban and apixaban for the treatment of acute UE‐DVT. Consecutive patients with VTE enrolled into the Mayo Clinic VTE Registry, between March 1, 2013 and December 31, 2019, were followed prospectively. Clinical, demographic and imaging data were collected at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…293 A more recent case control study comparing apixaban (n ¼ 63) or rivaroxaban (n ¼ 39) with LMWH and/or warfarin (n ¼ 108) concluded that DOACs appeared to be as safe and effective as LMWH and/or warfarin. 294 For patients with cancer associated UEDVT, long term LMWH monotherapy is preferred over the administration of VKAs. Anticoagulation therapy should be continued as long as the cancer remains active if the thrombotic event was not related to a CVC.…”
Section: Treatmentmentioning
confidence: 99%
“…293 A more recent case control study comparing apixaban (n ¼ 63) or rivaroxaban (n ¼ 39) with LMWH and/or warfarin (n ¼ 108) concluded that DOACs appeared to be as safe and effective as LMWH and/or warfarin. 294 For patients with cancer associated UEDVT, long term LMWH monotherapy is preferred over the administration of VKAs. Anticoagulation therapy should be continued as long as the cancer remains active if the thrombotic event was not related to a CVC.…”
Section: Treatmentmentioning
confidence: 99%
“…For example, there was an increased risk of thromboembolic and bleeding complications in patients with a mechanical heart valve treated with dabigatran in the RE-ALIGN study [ 45 ]. Data on direct oral anticoagulants (DOACs) for the treatment of UEDVT are very scarce, and include only small studies that mainly evaluated rivaroxaban ( Table 2 ) [ 17 , 46 , 47 , 48 , 49 , 50 ]. Nonetheless, since DOACs are recommended for patients with DVT of the lower extremities, these agents are increasingly being prescribed in patients with UEDVT [ 51 , 52 , 53 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In patients treated with LMWH or warfarin, there was one patient (0.9%) with recurrent thrombosis, three patients (2.8%) with major bleeding, and one patient (0.9%) with clinically relevant non-major bleeding. It is unclear how many patients were treated with apixaban or rivaroxaban [ 50 ]. Four studies evaluated rivaroxaban for UEDVT.…”
Section: Treatmentmentioning
confidence: 99%
“…apixaban, rivaroxaban, and edoxaban in malignancy-associated VTE; some physicians have used these data to argue use of DOACs in malignancy-associated UEDVT [44][45][46][47]. Direct data behind efficacy and safety of DOACs in UEDVT have been limited to very small studies [48][49][50][51][52]. Mechanistically, there is a question as to whether DOACs can appropriately treat foreign body-related thromboses e.g.…”
Section: Secondary Uedvt: Anticoagulationmentioning
confidence: 99%